The effect of earthquake frequency content and soil structure interaction on the seismic behavior of concrete gravity dam-foundation-reservoir system - H. Mohammadnezhad; N. Saeednezhad; P. Sotoudeh (Numerical Methods in Civil Engineering)
The effect of frequency content on the dynamic response of concrete gravity dams is investigated in this paper. Dams are one of the most complex structures to handle when there is dynamic analysis involved. One of the influential parameters on these structures' seismic response is the frequency content of the earthquakes. An index to represent frequency content, which represents frequency content  by PGA/PGV ratio(FCI) and sets three ranges including high(FCI>1.2), intermediate(0.8<FCI<1.2) and low-frequency content (FCI<0.8) is used in this paper. To simply study the effect of different frequency contents, a comparative analysis with different earthquake records with different frequency contents is performed on the finite element model of the Pine Flat concrete gravity dam. Results indicate a great influence of frequency content on the dynamic response of the structure. On a side note, to study the effect of soil-structure interaction, the same model has been analyzed under different modular ratios (modular ratio is the ratio of modulus of elasticity of the foundation of the structure Ef / Es. This is one of the simplest ways to introduce interaction effects in the analysis. The outcome states that different modular ratios (hence different soil-structure interaction participation) have an immense effect on the dam's dynamic response.